Without site investigation ground is a hazard (Thomas Telford, 1993)
This document raises awareness of the importance of ground, and highlights the consequences of inadequate site investigation. Case histories illustrate the consequences of inadequate site investigation.
Keywords: Engineering geology.; Building sites -- Evaluation.; elektronické knihy; electronic books